Tensile behaviour of an HDPE geogrid under cyclic loading: experimental results and empirical modelling. Issue 1 (31st August 2016) - Cardile, G.; Moraci, N.; Pisano, M.
Abstract : Residual deformations due to sustained and cyclic loading, acting on full-scale reinforced soil-retaining walls, could lead to an unacceptable serviceability limit state. In the present study, the writers carried out an extensive experimental programme comprising several monotonic and multistage tensile tests on a high-density polyethylene (HDPE) uniaxial extruded geogrid. Based on analysis of the test results, a combined empirical model has been developed that can predict the tensile behaviour of a specific HDPE geogrid subject to cyclic tensile loading. The paper presents the results and analyses of the effect of cyclic tensile loading histories (varying pre-stress tensile load, frequency, amplitude and number of cycles) on those parameters that are characteristic of hysteresis loops (i.e. the maximum and residual strains cumulated during each cyclic loading, tensile stiffness and area of the hysteresis loops). The results show that the average strain rate and the loading time affect the material's tensile response, as well as the combination of pre-stress tensile load and loading amplitude. The writers also investigated the difference between the load-strain relations for the monotonic test and those for the multistage tests, and concluded that the effects of cyclic loading histories are not due to material degradation.